KEGIATAN TES URINE SEBAGAI UPAYA P4GN DI INSTANSI PEMERINTAH OLEH BNNP JAWA TIMUR : (Studi Kasus di Kantor Bea Cukai Surabaya) - Ista Inassa (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2019)
Togetherness in realizing healthy Indonesia free of narcotics is a global action carried out to improve public health. Narcotics stands for Narcotics, Psychotropic and Other Addictive Materials. Other terms are drugs (narcotics, psychotoprics, and addictive substances). Drug abuse if not handled seriously from an early age, is feared to damage the future of the nation's next generation. This has invited the attention of the Indonesian government by making the implementing regulation of the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics, namely the restructuring of the National Narcotics Agency institutions in the Prevention and Eradication of Drug Abuse and Illicit Circulation (P4GN). Preventive measures in drug abuse can be done by detecting the content of drugs in the body. Urine is one of the samples most often used to examine the types of drug substances because it is considered the most accurate with the target, namely students, employees and the general public so that many urine test activities that use rapid tests. This research is a kind of qualitative descriptive and observational research. The study was conducted by collecting secondary data, observation, question and answer and participation. Based on the results of the analysis and discussion, it can be concluded that the report on the results of the activities of the section on prevention and community empowerment of the BNN East Java Province in 2017 shows the total activities carried out, namely times. In 2018, until August 2018 it is known that 220 activities have been carried out 220 times. The P2M field has implemented a full health promotion strategy, namely by using advocacy methods, fostering atmosphere and empowerment. Based on the results of observations and interviews conducted in urine testing activities at the Customs Office in Surabaya the urine test examination stage is in accordance with the technical guidelines in the field of community participation.